REARING OF LABEO BATA IN SEWAGE-FED FISH CULTURE POND - TRIPATHI, S. D.; DATTA, A. K.; BHOWMIK, M. L.; MANDAL, S. C. (Journal of Indian Fisheries Association, 2015)
Lq,beo bata is a highly priced fish which commanding good consumer preference, even if the size is very small (15 to 20 g each), especially in West Bengal. With a view to evaluating the culture potential of this fish, repeated experiments were conducted at the Wastewater Aquaculture Division of the Central Institute of Freshwater Aquaculture. Rahara, West Bengal, during 1991-93 in ponds fed with treated domestic sewage effluent. An average production of 1270.63 kg per ha was obtained within 6 to 10 months for a uniform stocking density of 50,000 seed per ha. The average size attained by the fish in the different sets of experiments varied from 23.3 to 37.9 g as against the initial weight of 0.096 to 0.193 g. Details of management, growth, survival, quantity of sewage used and pond nutrient status and productivity are dealt with in this communication.